Variation in Assignment of the COPD Patients into a GOLD Group According to Symptoms Severity - Moya-Álvarez V; Quevedo-Marín JL; Ji Z; Navarro-Jiménez C; Jiménez-García R; López-de-Andrés A; Pérez-Trullén A; de Miguel-Díez J (International Journal of COPD, 2020)
Virginia Moya-Álvarez,1 Juan Luis Quevedo-Marín,2 Zichen Ji,3 Cristina Navarro-Jiménez,4 Rodrigo Jiménez-García,5 Ana López-de-Andrés,6 Alfonso Pérez-Trullén,7 Javier de Miguel-Díez3 1Faculty of Medicine, Francisco de Vitoria University, Madrid 28223, Spain; 2Rey Juan Carlos University, Madrid 28922, Spain; 3Pulmonology Service, Gregorio Marañón University General Hospital, Madrid 28007, Spain; 4Pulmonology Service, El Escorial Hospital, Madrid 28200, Spain; 5Public Health and Maternal and Child Health Department, Faculty of Medicine, Complutense University of Madrid, Madrid 28040, Spain; 6Preventive Medicine and Public Health Teaching and Research Unit, Health Sciences Faculty, Rey Juan Carlos University, Madrid 28922, Spain; 7Pulmonology Service, Lozano Blesa University Clinical Hospital, Zaragoza 50009, SpainCorrespondence: Javier de Miguel-DíezPulmonology Service, Gregorio Marañón, University General Hospital, Madrid 28007, SpainTel +34 91 586 88 00Email jdemigueldiez@telefonica.netIntroduction: The Global Organization of Lung Disease (GOLD) classifies patients with chronic obstructive pulmonary disease (COPD) taking into account the symptoms. The modified Medical Research Council’s dyspnea scale (mMRC) and the COPD assessment test (CAT) are used to assess these symptoms. In this study, we analyze the concordance of GOLD classification using mMRC and CAT.Patients and Methods: This is an observational study of a cohort of 169 patients with COPD, who were classified following the GOLD 2017 recommendations, using both mMRC and CAT. A concordance analysis was applied, and a ROC curve was generated to identify the CAT score that best concorded with the mMRC scale.Results: The concordance for the GOLD groups classified by CAT and mMRC was moderate (kappa 0.492). For mMRC score of 1 and 2, a CAT score of ≥ 9 and ≥ 16 showed the maximum value of the Youden index, respectively. By reclassifying the patients with the new cut-off points obtained, the best concordance was obtained between the cut-off point for CAT of 16 and for mMRC of 2, followed by CAT of 9 and mMRC of 1.Conclusion: Because of the deficient concordance between CAT and mMRC, we propose the use of new cut-off points in future updates of the GOLD strategy.Keywords: chronic obstructive pulmonary disease, COPD, Global Organization of Lung Disease, GOLD, dyspnea, modified Medical Research Council, mMRC, COPD assessment test, CAT